"PREVALENCE OF PRE HYPERTENSION AND HYPERTENSION IN FIRST YEAR MEDICAL STUDENTS AND IT'S RELATION WITH BMI OF STUDENTS": - Dr. Mohit Malge; Dr. Chandrakant Waghmare (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Hypertension is a major global health concern, with pre-hypertension being a precursor. Medical students face unique stressors that may contribute to the development of hypertension. This study aimed to determine the prevalence of pre-hypertension and hypertension among first-year medical students and investigate its relationship with body mass index (BMI).Methods: A cross-sectional study was conducted among 228 first-year medical students at a medical college in Maharashtra. Participants were selected using systematic random sampling. Data were collected using a structured questionnaire and physical measurements, including blood pressure, height, and weight.Descriptive statistics, chi-square tests, independent t-tests, logistic regression, and multiple linear regression were used for data analysis.Results: The prevalence of pre-hypertension and hypertension was 29.8% and 7.9%, respectively. There was a significant association between BMI and blood pressure categories (p